Asteroidea (Echinodermata) from shallow-waters of the remote oceanic archipelago Trindade and Martin Vaz, southeastern Atlantic, with taxonomic and zoogeographical notes - Cunha, Rosana; Tavares, Marcos; de Mendonça, Joel Braga Jr (Zootaxa, 2020)
Trindade and Martin Vaz (TMV) is a highly isolated, oceanic volcanic archipelago located approximately 1200 km off the Brazilian coast and about 4200 km away from the nearest African coast. It has been almost 70 years since the first sea star, “Astropecten sp.”, was recorded from Trindade in 1951. In the following years (1955–1971; 2006) six sea star species were added to the archipelago’s fauna. After that period, however, research on shallow water echinoderms has not been conducted in TMV and no further sea star species have been recorded from there since. From 2012 to 2019, 263 daytime SCUBA diving and intertidal samplings conducted at TMV yielded 91 lots of sea stars in 7 species: Linckia guildingi Gray, 1840; Oreaster reticulatus (Linnaeus, 1758); Astropecten aff. antillensis Lütken, 1859; Copidaster lymani A. H. Clark, 1948; Luidia alternata alternata (Say, 1825); Mithrodia clavigera (Lamarck, 1816); and Ophidiaster guildingi Gray, 1840. The last five species in this list represent new records to the archipelago, with C. lymani also being the first record of the species in the southwestern Atlantic. Five shallow water species previously known from TMV have not been observed in the present survey: Asterinides folium (Lütken, 1860), Astropecten brasiliensis Müller & Troschel, 1842, Astropecten cingulatus Sladen, 1883, Linckia nodosa Perrier, 1875, and Ophidiaster alexandri Verrill, 1915. Twelve sea star species are currently known from shallow waters of TMV. A list of all sea star species known from shallow waters (intertidal down to 100 meters) of the tropical southern-central Atlantic oceanic archipelagoes and islands (Ascension, Cape Verde, Fernando de Noronha, Gulf of Guinea, Rocas Atoll, Saint Helena, Trindade and Martin Vaz) with their gross distribution in the Atlantic Ocean was compiled in order to explore the existence of patterns of geographic distribution for the shallow water sea star species in the tropical southern-central Atlantic oceanic islands. It has been found that 44% of the species from TMV are of western Atlantic affinity, 33% amphi-Atlantic, and 22% circumtropical in distribution. No endemic sea star species are known from TMV to date. The even more remote Ascension (ASC) and Saint Helena (STH) are more of a mosaic than TMV. The ASC and STH fauna consist of 8 and 11 sea star species, respectively. Their endemic component totals to 25% and 27%, respectively. STH has more amphi-Atlantic and eastern Atlantic sea star species (27% each) than ASC (25% and 12.5%, respectively). Twenty-five percent of the sea star species in ASC are circumtropical in distribution, whereas no circumtropical species have been found in STH. The western Atlantic (WA) component comparatively to the eastern Atlantic (EA) one is of minor significance in STH (18% versus 27%, respectively), whereas the WA and EA components contribute equally to the taxonomic composition in ASC (12.5% each). However, patterns of faunal affinities in both islands are actually taxon-dependent.